2023
DOI: 10.1021/acs.joc.2c02799
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Synthesis of Difluoromethyl Alkynes from Terminal and Silyl Acetylenes

Abstract: An efficient method for the direct C(sp)–H difluoromethylation of terminal alkynes and the desilylation–difluoromethylation of (trimethylsilyl)acetylenes is disclosed. The copper-catalyzed transformation provides access to a wide range of structurally diverse CF2H alkynes in good yields, utilizing a (difluoromethyl)zinc reagent and an organic oxidant. The difluoromethylation of important synthons and API’s is showcased. The synthetic utility of these (difluoromethyl)alkynes is demonstrated by selected cycloadd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…From 2015 to 2023, the effective trifluoromethylation or difluoromethylation of alkynes 40 , 42 , 45 and 47 using [Zn(CF 3 ) 2 (DMPU) 2 ] 4 a , [Zn(CF 3 ) 2 (bpy)] 6 or [Zn(CF 2 H) 2 (DMPU) 2 ] 4 f as fluoroalkyl source was described by the groups of Mikami, Li and Prakash (Scheme 10). [41–43] The experimental results showed that the reaction between alkynes 40 and [Zn(CF 3 ) 2 (DMPU) 2 ] 4 a in toluene at 80 °C for 12 h afforded the cyclopropenated products 41 a – c in 54–75 % yields [41] . However, the reaction system for product 41 c required the addition of 2 equivalents of PPh 3 under standard reaction conditions.…”
Section: Fluoroalkylation Of Compounds Using Well‐defined Fluoroalkyl...mentioning
confidence: 99%
See 2 more Smart Citations
“…From 2015 to 2023, the effective trifluoromethylation or difluoromethylation of alkynes 40 , 42 , 45 and 47 using [Zn(CF 3 ) 2 (DMPU) 2 ] 4 a , [Zn(CF 3 ) 2 (bpy)] 6 or [Zn(CF 2 H) 2 (DMPU) 2 ] 4 f as fluoroalkyl source was described by the groups of Mikami, Li and Prakash (Scheme 10). [41–43] The experimental results showed that the reaction between alkynes 40 and [Zn(CF 3 ) 2 (DMPU) 2 ] 4 a in toluene at 80 °C for 12 h afforded the cyclopropenated products 41 a – c in 54–75 % yields [41] . However, the reaction system for product 41 c required the addition of 2 equivalents of PPh 3 under standard reaction conditions.…”
Section: Fluoroalkylation Of Compounds Using Well‐defined Fluoroalkyl...mentioning
confidence: 99%
“…The Cu(CH 3 CN) 4 BF 4 ‐catalyzed radical bis(trifluoromethylation) reaction of alkynes 42 or 1,3‐enynes 45 using Togni′s reagent II 43 as well as [Zn(CF 3 ) 2 (bpy)] 6 in CH 3 CN at room temperature for 12 h furnished the corresponding 1,2‐bis(trifluoromethylated) alkenes 44 and 1,4‐bis(trifluoromethylated) allenes 46 in satisfactory yields ( 44 : 58–84 %, 46 : 46–93 %) [42] . Prakash and co‐workers showed that the CuBr‐catalyzed direct C(sp)−H difluoromethylation of terminal alkynes and the desilylation‐difluoromethylation of (trimethylsilyl)acetylenes using [Zn(CF 2 H) 2 (DMPU) 2 ] 4 f as difluoromethyl source in the presence of LiO t Bu and 9,10‐phenanthrenequinone afforded difluoromethyl alkynes 48 in up to 80 % isolated yields [43] . However, due to the volatility of products 48 a and 48 b , the authors determined their yields to be 56 % and 22 % respectively through 19 F NMR, but did not separate them.…”
Section: Fluoroalkylation Of Compounds Using Well‐defined Fluoroalkyl...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the substrate scope is limited to aromatic alkynes. Very recently, Prakash demonstrated that a catalytic copper enables oxidative difluoromethylation of terminal alkynes. However, this process involves a multistep reaction operation; besides, a strong base and oxidant are all required.…”
mentioning
confidence: 99%
“… This [Cu I –CF 2 H] intermediate is believed to be generated in situ through a transmetalation between Vicic–Mikami , reagent 2 and Cu I ( I ). Then, in the presence of alkynyl bromides, a prominent electrphile, allowing oxidation to key intermediate VI . , Subsequently, this intermediate undergoes reductive elimination to forge the desirable difluoromethylated allynes product VII . This reductive elimination step would simultaneously regenerate the CuI catalyst, effectively closing the catalytic cycle.…”
mentioning
confidence: 99%